Diagnostic dilemma in skin adnexa malignancy: a rare case report with review of literature - C. A., Shashirekha; ., Krishnaprasad; Reddy, Sandeep; P. N., Sreeramulu; T., Pramod; Kiran, Ravi; R., Deepthi (International Surgery Journal, 2018)
Apocrine malignancies are rare to occur. Axilla and the anogenital skin are the most common sites of primary tumour. Apocrine malignancy carries high risk of lymphatic and vascular spreading to lung, liver and bone. A 40 years old painter, presents with diffuse swelling and pain in the left lower limb up to left inguinal region since 5 to 6 months. With generalised lymphadenopathy. On evaluation, revealed adenocarcinoma of apocrine, skin adnexa in the extremities of the limb with extensive distant metastasis. Apart from Dermatologists other board specialty consultant should be aware of the possibility of apocrine adenocarcinoma while differentiating cutaneous tumor located in the extremities. Apocrine malignancy should be treated aggressively with wide local excision or amputation the involved part for improving the life expectancy. Since prevalence of apocrine malignancy are rare, and it is associated with increased mortality, it provoke us the field of research for discovering other modalities of treatment.